The improvement conception of drivers training and examination system in Lithuania - Valiūnas, Valdas; Pečeliūnas, Robertas; Nagurnas, Saulius; Žuraulis, Vidas; Kemzūraitė, Kristina; Subačius, Rimantas; Lazauskas, Jonas (Transport, 2011)
The current paper presents the structure of the drivers training and examination system existing in Lithuania and describes the interrelations between the institutions involved in the said process. In course of analysis of models of drivers training and examination systems of various countries, their advantages and imperfections are highlighted. The experience of Germany, Holland, Sweden and Great Britain in the sphere of training and examination of motor vehicles drivers is described. In the end of the paper, conclusions and recommendations for improving the quality of drivers training and examination system as well as traffic safety in Lithuania are provided. First Published Online: 07 Jul 2011